Estrutura da comunidade de copépodes (crustacea: copepoda) em um gradiente longitudinal ambiental no sistema rio-planície de inundação do Alto rio Paraná - Palhiarini, Welinton Sousa (2016)
The construction of reservoirs has intensified in recent decades, mainly due to increased demand in power generation and supply. However, the installation of these projects causes environmental change on biotic and abiotic components and cause reduction of flood pulses in floodplains associated with dammed rivers. In rivers like the Paraná River basin, there are a number of reservoirs in cascade that causes changes in environmental variables. Thus, the dynamic system that is understood according to the Continuum Concept Reservoir Cascade (CRCC). Among the zooplankton, copepods have been used in several studies that show the influence of the construction of reservoirs in aquatic environments because the distribution of these organisms is influenced by environmental factors and provide rapid response to environmental changes because of its short life cycle. Thus, the copepods can be used as bioindicators to measure the environmental quality of ecosystems. Moreover, by presenting migratory movements, not only have great scope in the dammed river, but also in adjacent environments and tributaries. The copepod community structure along rivers has been continuously studied with these microcrustaceans the river-floodplain system of the upper Paraná River, as well as the influence of the cascade of reservoirs on the attributes of this community. Thus, the study of copepod community structure in this system, it is important to check and indicate the impact on the river, adjacent environments and tributaries under the influence upstream of the dam of Porto Primavera. This work consisted of a general introduction and an article. The general introduction addressed the main problems related to the construction of dams on aquatic communities and in particular on the zooplankton community, with emphasis on copepods. The Article corresponds to the study of the copepod community river-floodplain system in the upper Paraná River, between the dam of Porto Primavera and Itaipu reservoir. Thus, the attributes of the copepod community (abundance of organisms, richness and diversity of species) were evaluated along a longitudinal environmental gradient in this system.